Mining User Generated Contents in Online Healthcare forum using Text Mining Techniques (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of online health care forum patients and health seekers can access the Internet and get health related information through their social media blogs and health care forums. These forum users are involved to post emotional based messages and health related posts. In this forum enormous amount of emotional based messages posted by different stakeholders that are patients, caregivers and healthcare experts. In this online healthcare forum patients /healthseekers post a question. Peers who reply to the questions asked that replies are based on more emotions oriented messages. For analyzing these messages to find the adoption based answers , Stakeholders and Topic identification in the messages and Sentiments (emotions)  to the messages. For this Framework we use various text mining  methods as preprocessing , NLP methods ,and Machine learning algorithms as SVM- RBF(radial Basis Function) Classification , K-medoid clustering method and Lexicon Data Analysis (LDA) is used .In this paper Medhelp online healthcare forum messages were taken up for analysis.